Europarl: Swedish - Språkbanken Text (University of Gothenburg, 2024)
The Swedish part of European Parliament Proceedings Parallel Corpus

Svenska delen av European Parliament Proceedings Parallel Corpus
Europarl: svenska
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik